Factors Associated With Emergency Department Visits for Migraine: An Observational Study. Issue 10 (23rd October 2014) - Minen, Mia T.; Loder, Elizabeth; Friedman, Benjamin
Abstract : Objective/Background: This study aims to determine why patients with migraine present to an emergency department (ED). While migraine accounts for over 800, 000 ED visits annually, no prospectively gathered data characterize patients' reasons for presenting to an ED. Methods: We prospectively interviewed 309 consecutive patients presenting to an urban ED for headache. Patients were asked 100 closed‐ended questions regarding sociodemographics, headache history, and current headache attack. We performed descriptive analyses on patients fulfilling International Classification of Headache Disorders 2 migraine criteria. Results: Of 186 patients who met migraine criteria, 77% (95% confidence interval [CI]: 71, 83%) had a primary care provider (PCP), 87% (95% CI: 82, 92%) had medical insurance, and 83% (95% CI: 77, 88%) had drug coverage. Fifty‐three percent (95% CI: 46, 60%) reported that they previously visited a doctor for headache. Fifty‐five percent (95% CI: 48, 62%) previously received a migraine diagnosis. Twenty‐two percent (95% CI: 16, 28%) sought medical care for the current headache prior to ED presentation. Fifty‐five percent (95% CI: 48, 63%) took abortive medication for migraine on the day of the ED visit. Median headache duration was 24 hours (IQR: 12‐72). Forty‐nine percent (95% CI: 42, 57%) screened positive for depression. The most common reason for visiting the ED was a perceived emergency condition or referral by a physician (33.3% [95% CI: 27, 40%]). Other commonly cited reasons related to access to care. Conclusions: Most migraineurs presenting to the ED have a PCP and health insurance. ED visits commonly result from an inability to access care elsewhere and because patients consider pain to be an emergency condition. Missed opportunities for diagnosis and treatment likely contribute to ED visits.